How many cases are required to achieving early proficiency in purely off-clamp robot-assisted partial nephrectomy? - Zhang, Guoling; Wang, Bowen; Liu, Hua; Jia, Guang; Tao, Boju; Zhang, Haoxun; Wang, Chunyang (Frontiers in Surgery, 2024)
Background and purpose: Off-clamp robot-assisted partial nephrectomy (Offc-RAPN) is a technically challenging procedure that can effectively avoid renal ischemia owing to the absence of hilar vessel preparation and clamping. However, data on the learning curve (LC) for this technique are limited. The purpose of this study was to assess the LC of Offc-RAPN and compare the perioperative outcomes between different learning phases.Methods: This retrospective study included 50 consecutive patients who underwent purely Offc-RAPN between January 2022 and April 2023. Multidimensional cumulative sum (CUSUM) analysis method was used to assess LC. Spearman's correlation and LOWESS analysis were performed to analyze the continuous variables of perioperative outcomes. Baseline characteristics and perioperative outcomes were compared using  2 test, t test and U test.Results: CUSUM analysis identified two LC phases: phase I (the first 24 cases) and phase II (the subsequent 26 cases). Phase II showed significant reductions in mean operative time (133.5 vs. 115.31 min; p=0.04), mean console time (103.21 vs. 81.27 min; p=0.01), and mean postoperative length of stay (5.33 vs. 4.30 d; p=0.04) compared to phase I. However, no significant differences were observed in other perioperative outcomes or baseline characteristics between the two LC phases.Conclusions: Offc-RAPN performed by a surgeon with experience in laparoscopic and robotic surgeries achieved early proficiency in 24 cases. Moreover, Offc-RAPN alone is safe and feasible even in the initial phase of the LC for an experienced surgeon.